2014
DOI: 10.1158/1541-7786.mcr-14-0242
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Pool of Tetraspanin CD9 Contributes to Mitotic Processes in Human Breast Carcinoma

Abstract: Tetraspanin-29 (CD9) is an integral membrane protein involved in several fundamental cell processes and in cancer metastasis. Here, characterization of a panel of breast cancer cells revealed a nuclear pool of CD9, not present in normal human mammary epithelial cells. Antibody binding to surface CD9 of breast cancer cells resulted in increased nuclear CD9 fluorescence. CD9 was also found, along with a plasma membrane-associated pool, in the nuclei of all primary ductal breast carcinoma patient specimens analyz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…The intracellular pathway used by EV-derived biomaterials en route to the nucleus is also in line with studies showing new endosomal pathways that deliver surface proteins to the nucleus [44, 45]. Such mechanism might explain the presence of EV-associated proteins and nucleic acids in nuclei of target cells [1719], and the atypical nuclear localization of CD9 and CD133 in cancer cells [46, 47]. …”
Section: Discussionsupporting
confidence: 55%
“…The intracellular pathway used by EV-derived biomaterials en route to the nucleus is also in line with studies showing new endosomal pathways that deliver surface proteins to the nucleus [44, 45]. Such mechanism might explain the presence of EV-associated proteins and nucleic acids in nuclei of target cells [1719], and the atypical nuclear localization of CD9 and CD133 in cancer cells [46, 47]. …”
Section: Discussionsupporting
confidence: 55%
“…Finally, other as yet unknown pathways could be involved in CD9 dependent regulation of AR activity due to the pleotropic effects of tetraspanins. The latter hypothesis is supported by recent results [ 88 ] showing nuclear localization of both CD9 and IGSF8 in breast carcinoma cells. That study showed that nuclear CD9 may be involved in regulation of mitosis, therefore IGSF8 inhibition may activate CD9 effects on both cell division and AR transcriptional regulation.…”
Section: Discussionsupporting
confidence: 76%
“…Therein, EV‐associated cargo molecules can modify the gene expression of the host cells. These surprising findings are in line with numerous studies showing the atypical nuclear localization of the EV‐associated proteins CD9 and CD133 as well as the shuttling of proteins and nucleic acids to nucleoplasm of recipient cells . Recently, we described that two proteins, ie vesicle‐associated membrane protein‐associated protein A (VAP‐A) and the cytoplasmic oxysterol‐binding protein‐related protein 3 (ORP3), are essential for the entry and the tethering of late endosomes to nuclear envelope invaginations of type II (Figure B).…”
Section: Introductionsupporting
confidence: 84%